IMPERFECT COMPETITION IN THE PRIMARY AGRICULTURAL COMMODITY MARKET IN SERBIA - Paraušić, Vesna; Mihailović, Branko; Hamović, Vladana (Economic Annals, 2010)
Development of the primary agricultural production sector in the Republic of Serbia is predominantly restricted by a disorganised and inefficient market of purchase of primary agricultural products. The government should be held responsible for this, because its existing legislation and law-implementing instruments and institutions are failing to secure a healthy market economy. In the future the country will have to demonstrate systematic activity towards regulating and developing the agricultural commodity market, and provide an input for agricultural production. This onlyrepresents the first step, yet nevertheless it is the essential prerequisite for developing a competitive agricultural sector in Serbia.